Detection of antibodies against leptospira serovars in dogs and cats in an indigenous village, Belum, Perak - Choong, Jia Jie (2018)
Leptospirosis is a re-emerging disease that affecting both human and animals. Despite the high incidence, limited study has been conducted in Malaysia especially in indigenous population. A recent outbreak of herpangina viral infection in year 2015 that wiped out almost half of the population of the indigenous children in the village has raised the public health concern. The targeted area of this study located at Tiang River, Belum state, Perak. Presence of large water bodies (man-made lake), exposure to the wildlife such as rats and living in vicinity with ownerless dogs and cats predispose this indigenous people to leptospirosis in the area. In this study, 40 samples (37 dogs and 3 cats) were collected to detect the presence of leptospiral infection of canine and feline leptospirosis status in the area and identify the predominant serovars. Microscopic agglutination test (MAT) was used to determine the presence of anti-leptospiral antibodies in the serum samples collected. The testing panel included 12 common serovars of leptospira: Canicola, Pomona, Icterohaemorrhagiae, Grippotyphosa, Australis, Pyrogenes, Lai, Celledoni, Bataviae, Javanica, Hardjoand Copenhageni. Three out of 37 dogs (8.1%) and one out of three cats (33%) were seropositive for Leptospira at the cut-off titer of 1:100 by following World Organisation for Animal Health (OIE) standard. Celledoni 5.4% (n=2/37) was found to be the most predominant serovar, followed by Australis 2.7% (n=1/37) and Lai 2.7% (n=1/37) among the dogs studied while Lai 33% (n=1/3) was found in cat as the only predominant serovar. These findings alerted that potential zoonosis risk of spreading leptospirosis from the animals to the indigenous people and also presence of leptospira in their living environment. Further study and investigation are crucial to evaluate the epidemiology of leptospirosis in the area.